2023
DOI: 10.1097/md.0000000000033930
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-to-lymphocyte ratio as a determinant of survival in patients with gastric cancer undergoing gastrectomy: A cohort study

Abstract: The monocyte-to-lymphocyte ratio (MLR) is an important prognostic determinant of various malignancies. However, the prognostic role of MLR in patients with gastric cancer undergoing gastrectomy remains unclear. Patients with stage I to III gastric cancer who underwent curative-intent gastric resection were enrolled in this study. Cox regression analysis was used to determine the independent variables for overall survival (OS) and disease-free survival (DFS). The established models were validated internally. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…This reflects a state of enhanced inflammation and reduced immunity, which favors tumor progression. Studies have shown that MLR is a valuable marker for the diagnosis and prognosis of various cancers including colorectal ( 22 ), breast ( 23 ), and gastric ( 24 ) cancers. According to our research, the MLR serves as a separate predictive element for individuals diagnosed with stage IIIC1p cervical cancer, and a higher preoperative MLR value corresponds to a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects a state of enhanced inflammation and reduced immunity, which favors tumor progression. Studies have shown that MLR is a valuable marker for the diagnosis and prognosis of various cancers including colorectal ( 22 ), breast ( 23 ), and gastric ( 24 ) cancers. According to our research, the MLR serves as a separate predictive element for individuals diagnosed with stage IIIC1p cervical cancer, and a higher preoperative MLR value corresponds to a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%